THE JUDGMENT IN LIEU OF THE CONTRACT - INTERPRETATION AND APPLICATION OF ARTICLES 1279 AND 1669 OF THE CIVIL CODE RELATING TO THE PROMISE OF SALE - Emilian-Constantin MEIU (Challenges of the Knowledge Society)
The matter of enforcement in the promise of sale poses practical problems arising from the interpretation of the articles 1279 and 1669 of the Civil Code and that we intend to analyze in this study. Among the issues to analyze we can mention: the role of the court and the legal requirements for a judgment in lieu of contract as follows: execution of their duties by the party calls for a judgment in lieu of the contract; the unjustified refusal of the promissor-seller to conclude the contract of sale within the set deadline; establishing the fulfillment of the terms of sale at the time of the judgment; the quality of the promise-seller of the owner of the good; the filing of the fiscal certificate issued by the specialized department of the local public administration authority resulting in the lack of debts of the promised property owner; proof of up-to-date flows of contribution allowances to the owners expenses. We will now consider the prescription of the right to request a decision in lieu of contract under article 1669 para. (3) Civ. Code, as well as the importance of the inalienability clause in the conventions which give rise to the obligation to pass on the property in the future to a determined or determinable person, as provided by article 627 par. (4) Civ. Code.